Addition of new flammulina species via DNA, molecular characterization and phylogenetic investigation: New species records in Genus Flammulina - Jabeen, Nadia; Lodhi , A. Mubeen; Gul, Alia; Basit, Abdul; Almowallad, Sanaa; Alalawy, Adel I.; Alharbi, Amnah A.; Sakran, Mohamed; Ercisli, Sezai; El-Sharnouby, Mohamed; El Sabagh, Ayman (Cellular and Molecular Biology, 2024)
Flammulina was found frequently distributed in the District Mansehra during the present research work. The genus was ignored and not studied for prevalence previously, as F. velutipes was the exclusively reported species from the research vicinity. During the present research work, three new species were explored i-e F. hazariansis (N. J201177, N. J201178), F. solatium (N. J201188, N. J201167) and F. dwarftype (N. J201187, NJ201139) were amassed from the surrounding areas of Hazara University Mansehra. Our findings revealed that the reported species are novel, the molecular, morphological, and phylogenetic characterizations proved it. The specimens were collected from various habitats, vegetation, damp places, and forest areas with rich organic soil favor the mushroom’s growth from May to November. The species were studied for morphological characteristics like size, shape and color of the pileus, stripe, and spore size were also recorded. The species were preserved by sun and oven drying strategies. The Kit methods for molecular characterizations were used for the extraction of DNA, and for PCR, ITS4 primer was designed from conserved regions described in previous studies. The amplified PCR products were sequenced from Microgen Korea. Phylogenetic analysis of the obtained sequences was done based on the maximum likelihood method using Mega version 6.0. Our findings based on morphological and phylogenetic analysis confirmed the existence of three new species in the already described genera from the region. The area of District Mansehra is enriched with natural vegetation and can be explored for brand-spanking new species.